Generational Determinants of Manual Annual Tax Return Filing: A Mixed-Methods Study of Individual Taxpayers at DJP East Java II - Adhara Damayanto Putri; Asqolani Asqolani (Polytechnic of State Finance STAN, 2025)
This study aims to analyze the profile of individual taxpayers who submit their Annual Tax Return (SPT) manually based on generational cohorts within the jurisdiction of Kantor Wilayah Direktorat Jenderal Pajak (DJP) Jawa Timur II. The background of this research is based on the persistent high number of taxpayers filing their SPT manually, despite the availability of a more efficient electronic reporting facility (E-filing) provided by Direktorat Jenderal Pajak. A descriptive qualitative method with an inductive approach was employed, utilizing primary data collected through interviews with tax advisor officers of Kantor Wilayah Direktorat Jenderal Pajak Jawa Timur II and open-ended questionnaires distributed to 102 respondents representing the Baby Boomer, X, Y, and Z generations, as well as secondary data from Kantor Wilayah Direktorat Jenderal Pajak Jawa Timur II. The results reveal a significant decline in the number of manual filers from the 2021 to 2023 tax years; however, the highest proportion of manual filers remains concentrated among the Baby Boomer generation, who are generally more reluctant to adopt new technologies. Conversely, Generations Y and Z demonstrate a marked increase in the use of electronic filing, which aligns with their strong familiarity and comfort with digital technology. Key factors influencing the preference for manual filing include entrenched habits, perceptions of the complexity of online systems, limited internet infrastructure, and insufficient technical understanding. These findings highlight the necessity of developing more adaptive, generation-based outreach strategies to accelerate the transition toward fully electronic tax reporting, thereby enhancing both the efficiency of tax administration and taxpayer compliance.